POR UMA ESTÉTICA DA ANCESTRALIDADE: A relação entre categorias da estética iorubá e o grupo de dança afro Abanjá - SILVA, Jefferson Gabriel Moreira da (2025)
Or this dissertation aims to relate aesthetic categories of Yoruba culture to the process of creating the performance ORIXÁS NA ÁFRICA by the group Abanjá. Methodologically, the research is based on crossroads, oral literature, and itanlogy. The research findings revealed that in the process of constructing the performance, the body adopts the role of producer of epistemologies and aesthetics. The conclusion is that one of the points of intersection between ethics, art, and politics in the production of ORIXÁS NA ÁFRICA (1996) is the creation of aesthetics rooted in ancestry.